PORTRAIT OF THE KINDERGARTEN TEACHER IN THE SOCIAL AND CULTURAL SPACE OF THE MODERN RUSSIA - Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the problem of actual requirements to the kindergarten teacher, which are imposed by society (state), educational organization, the family of the pupil and children of preschool age. The author analyzes the provisions of a number of documents regulating the activities of the teacher, systematizes the results of scientific research about the role of the teacher in modern preschool education. The article describes the theoretical model of the way of the teacher of the preschool educational organization in modern social and cultural conditions: mission, function, result, –answering the question "What should be a modern kindergarten teacher?". The results of the study can be used as a basis for the modernization of the content of the professional activity (professional standard) of the modern teacher of a preschool educational organization.The article is intended for public reading and for those who are interested in pedagogical research.